2008
DOI: 10.1108/00346650810920187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soaking and cooking on nutritional quality and safety of legumes

Abstract: PurposeLegumes are widely grown and are consumed as a source of plant protein throughout the world. They rank second after cereals with respect to their consumption order. Legumes have anti‐nutritional factors which make their uses limited. This study aims to check the effect of soaking and cooking on the anti‐nutrient contents and nutritional quality of the legumes.Design/methodology/approachFive legumes (white kidney bean, red kidney bean, lentil, chickpea, and white gram) frequently used by the masses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 14 publications
3
36
0
4
Order By: Relevance
“…This hindered bioavailability of the nutrients such as iron due to presence of phytate. Similar cases were reported from other studies [16,17,24,25] where they observed that soaking beans reduced phytate and resulted in improved bioavailability of iron. Cooking beans for a long time at high temperatures can destroy protein [17].…”
Section: Soaking and Fermentationsupporting
confidence: 78%
“…This hindered bioavailability of the nutrients such as iron due to presence of phytate. Similar cases were reported from other studies [16,17,24,25] where they observed that soaking beans reduced phytate and resulted in improved bioavailability of iron. Cooking beans for a long time at high temperatures can destroy protein [17].…”
Section: Soaking and Fermentationsupporting
confidence: 78%
“…The reduction in protein content after soaking was found to be 18.69% in chickpea genotypes. Huma et al, (2008) reported that reduction in protein content (14.78 -21.83 %) after cooking the presoaked legumes might be attributed to partial removal of essential as well as non -essential amino acids with other nitrogenous compounds formed as a result of chemical degradation of protein into water soluble amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers report 9-18 mg/g PA for Weld-grown chickpea in Spain [31,32], 5.8-10 mg/g for Weld-grown chickpea in Egypt [22], 8.2 mg/g in Brazil [33], 2.3-6 mg/g for Weldgrown chickpea in Pakistan [34], 18 mg/g for Weld-grown chickpea in northern USA [35], and 9.8 mg/g in Weldgrown chickpea cotyledons from India [8], all from diVerent extraction methodology.…”
Section: Phytic Acidmentioning
confidence: 99%